In the Pipeline : Georgia's Oil and Gas Transit Revenues - Dunn, Jonathan (IMF Working Papers; Working Paper ;, 2004)
Starting in 2005, nontax revenue in Georgia is expected to rise significantly, in the form of transit fees for oil transported through the Baku-Tbilisi-Ceyhan Oil Pipeline. Transit fees for gas transported through the South Caucasus Pipeline are expected to start in 2007. This paper discusses (1) how much additional revenue can be expected, (2) prospects for monetizing gas that could be received as in-kind transit fees, in the light of pervasive nonpayment in the domestic gas sector, (3) the impact of these inflows on external competitiveness, (4) how to put in place appropriate reporting on these additional revenues, and (5) whether these inflows justify the creation of a special natural resource fund.